2020
DOI: 10.1098/rsta.2019.0447
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and superficial transport of oil on biological and bionic superhydrophobic surfaces: a novel technique for oil–water separation

Abstract: Superhydrophobicity is a physical feature of surfaces occurring in many organisms and has been applied (e.g. lotus effect) in bionic technical applications. Some aquatic species are able to maintain persistent air layers under water ( Salvinia effect) and thus become increasingly interesting for drag reduction and other ‘bioinspired’ applications. However, another feature of superhydrophobic surfaces, i.e. the adsorption (not absorption) and subsequent superficial transportation and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…A recent study has revealed that commercial flock and textiles treated with a hydrophobic agent (TEGOTOP 210) show excellent self‐driven oil absorption that does not require an external driving force. [ 85 ] This finding lays a foundation for developing oil–water separation technologies and materials. Moreover, the natural Salvinia blade provides a theoretical basis for bionics and a more environmentally friendly, efficient, feasible, and thorough method of cleaning up oil pollution.…”
Section: Applications Of Artificial Salvinia Surfacesmentioning
confidence: 93%
“…A recent study has revealed that commercial flock and textiles treated with a hydrophobic agent (TEGOTOP 210) show excellent self‐driven oil absorption that does not require an external driving force. [ 85 ] This finding lays a foundation for developing oil–water separation technologies and materials. Moreover, the natural Salvinia blade provides a theoretical basis for bionics and a more environmentally friendly, efficient, feasible, and thorough method of cleaning up oil pollution.…”
Section: Applications Of Artificial Salvinia Surfacesmentioning
confidence: 93%
“…[1][2][3] It is a vitally urgent task for scientists all over the world to develop advanced strategies for handling the oily wastewater, particularly for surfactant-stabilized micro/ nano-sized emulsions. 4 Until now, several techniques such as coalescence, 5 oil skimming, 6 biological treatment 7 and flotation 8 and so forth, have been used for oily wastewater to obtain purified water, yet they have many disadvantages cannot be ignored, including require excessive energy consumption, poor selectivity, high cost and complex instruments. 9,10 In the past few years, more and more attention has been paid to investigations applying and preparing materials with special super-wetting properties for oily wastewater management.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PHCs in water forms a film that could prevent oxygen entry, leading to the death of aquatic organisms (Faustorilla et al, 2017). This has inevitably been of major concern over some decades and has raised the need for PHCs remediation of surface and groundwater in which physical and chemical methods such as the dissolved air flotation, use of skimmers, barriers, booms, dispersant, or surfactant spray have been employed, whereas the biological and thermal techniques were based on bioaugmentation, and burning of crude oil, respectively (Barthlott et al, 2020;Liu et al, 2021;Navarathna et al, 2020;Tran et al, 2021). Although these methods have proven effective, major challenges including the formation of toxic polycyclic aromatic hydrocarbons (PAHs) through oxidation, the limitation of microorganisms to perform due to PAHs, and high cost have limited their wide application (Bhattacharya et al, 2018;Bianco et al, 2021;Fuentes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%